A method for producing high-strength oxygen-free copper rods

By introducing chromium and cerium into copper rods and coating them with a phosphorus-nickel layer, combined with glow discharge plasma furnace treatment, the problem of insufficient strength and toughness of copper rods was solved, and high-strength oxygen-free copper rods were prepared to meet the application requirements of high conductivity.

CN122629341APending Publication Date: 2026-08-25JIANGXI HONGZI IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610806297.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-05
Publication Date
2026-08-25

AI Technical Summary

Technical Problem

Existing technologies struggle to improve the strength and mechanical properties of copper rods while maintaining their high conductivity, especially in applications requiring high conductivity, where the tensile strength and toughness of copper rod materials are insufficient.

Method used

By introducing chromium and cerium into the copper matrix, fine metal compounds are formed. Then, by coating with a phosphorus-nickel layer and combining it with glow discharge plasma furnace treatment, the additive powder is rapidly fused with the copper melt, reducing defects. The chemical phosphorus-nickel plating process and activation treatment are used to form non-uniform nucleation points, thereby improving the material strength.

Benefits of technology

The prepared oxygen-free copper rod material exhibits high tensile strength and good toughness, which can meet the mechanical performance requirements of modern industry for high-quality copper materials, and the strength is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122629341A_ABST
    Figure CN122629341A_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing high-strength oxygen-free copper rods, and steps of the method comprise the following steps: (1) screening copper-chromium intermediate alloy powder and copper-cerium intermediate alloy powder, mixing, cleaning and degreasing, alkali washing, and obtaining cleaned powder; (2) pickling the cleaned powder, activating, and chemically plating phosphorus-nickel to obtain composite powder coated with phosphorus-nickel; (3) carrying out glow plasma heat preservation and pressure preservation treatment on the composite powder coated with phosphorus-nickel to obtain additive powder; (4) melting cathode copper blocks, adding the additive powder after melting, carrying out electromagnetic stirring, casting into ingots, and covering graphite scales after casting to cool; and (5) carrying out homogenizing annealing treatment on the cooled ingots to obtain the high-strength oxygen-free copper rods. The oxygen-free copper rods prepared by the method have good strength, i.e., high tensile strength, and can better adapt to the requirements of modern industry on the mechanical properties of high-quality copper materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-quality copper materials technology, and in particular to a method for preparing high-strength oxygen-free copper rods. Background Technology

[0002] Oxygen-free copper, due to its excellent electrical and thermal conductivity, machinability, and corrosion resistance, is widely used in electronics, electrical engineering, communications, rail transportation, and high-end equipment manufacturing, especially in the production of copper rods, wires, and busbars requiring high conductivity. With the increasing demand for high-performance conductor materials from downstream industries, particularly in new energy vehicles, high-speed railways, precision electronic components, and ultra-high voltage power transmission and transformation equipment, copper rod materials are required to possess not only extremely high conductivity but also high tensile strength, good toughness, and fatigue resistance. To improve the strength of copper rods, adding trace alloying elements and second phases for strengthening is one of the most widely researched and partially industrialized methods. The theoretical basis of this method is: while maintaining the high conductivity of the copper matrix, introducing small amounts of other alloying elements and second phases, and improving the mechanical properties of the copper rod through solid solution strengthening, grain refinement strengthening, precipitation strengthening, or second phase strengthening mechanisms. Summary of the Invention

[0003] Therefore, the present invention provides a method for preparing high-strength oxygen-free copper rods, the steps of which include: (1) The copper-chromium master alloy powder and the copper-cerium master alloy powder are sieved separately, and the sieved powders are collected and mixed evenly to obtain a mixed powder. The mixed powder is added to acetone, cleaned and degreased under ultrasonic environment, then the solid and liquid are separated, the solid phase is dried, and the dried solid phase is added to a composite solution of sodium hydroxide, trisodium phosphate and sodium silicate for alkaline washing. After alkaline washing, the solid and liquid are separated, the solid phase is washed with deionized water and dried to obtain the cleaned powder. (2) The cleaned powder is added to oxalic acid solution for pickling treatment. After pickling, solid-liquid separation is performed, solid phase is washed and dried. The dried solid phase is mixed with sieved zinc powder. Then the mixture is added to an activation solution for activation treatment. After activation, solid-liquid separation is performed, solid phase is washed and dried. Then, phosphorus-nickel plating is performed to obtain a phosphorus-nickel coated composite powder. (3) The phosphorus-nickel composite powder is laid on the cathode plate of the glow plasma furnace. The phosphorus-nickel composite powder is covered with a titanium mesh. After the furnace is covered, the air inside the furnace is extracted and a mixture of hydrogen and argon is introduced as a reducing atmosphere. The voltage and duty cycle are set to start glow plasma. After the temperature rises to a specific value, the furnace is kept warm and pressure is maintained. After the process is completed, the gas supply is turned off and the furnace is cooled to obtain the additive powder. (4) The cathode copper block is heated and melted in a vacuum medium frequency induction furnace. After melting, the additive powder is added, and after being electromagnetically stirred evenly, it is cast into an ingot. After casting, it is covered with graphite flakes and cooled. (5) The cooled ingot is annealed to obtain the high-strength oxygen-free copper rod.

[0004] Further, in step (1), the copper-chromium master alloy powder has a chromium mass percentage of 10% and the remainder is copper; the copper-cerium master alloy powder has a cerium mass percentage of 20% and the remainder is copper.

[0005] Further, in step (1), the mass ratio of the sieved powder mixture is copper-chromium master alloy powder: copper-cerium master alloy powder = 10:2-3; in the composite solution of sodium hydroxide, trisodium phosphate, and sodium silicate, the concentration of sodium hydroxide is 16-18 g / L, the concentration of trisodium phosphate is 20-25 g / L, the concentration of sodium silicate is 5-8 g / L, and the solvent is water; the alkaline washing temperature is 80±5℃, the alkaline washing time is 5-6 min, and condensation and reflux are carried out during the alkaline washing process.

[0006] Further, in step (2), the concentration of oxalic acid in the oxalic acid solution is 8-10 g / L, the solvent is water, and the pickling time is 100-120 s; the activation process is as follows: first, a mixed aqueous solution of sodium citrate, citric acid, and nickel chloride is prepared as the activation solution, the solution is heated to 70±5℃ in a water bath and kept at that temperature, and then refluxed; then the mixture is added to the solution, and after the addition is completed, the temperature is kept at 70±5℃ for 90-120 s to complete the activation; the sieved zinc powder is zinc powder that has passed through a 500-mesh sieve, and the mass ratio of the dried solid phase to the sieved zinc powder is 10:6-8.

[0007] Further, in the mixed aqueous solution of sodium citrate, citric acid, and nickel chloride, the concentration of sodium citrate is 120-130 g / L, the concentration of citric acid is 80-85 g / L, and the concentration of nickel chloride is 3-4 g / L; the ratio of the mixture added to the mixed aqueous solution of sodium citrate, citric acid, and nickel chloride is 1 g: 50 mL.

[0008] Further, in step (2), the concentrations of each component in the electroless phosphorus-nickel plating solution are as follows: NiSO4·6H2O 20-25 g / L, NaH2PO2·H2O 25-28 g / L, sodium citrate hydrate C6H5Na3O7·2H2O 14-15 g / L, succinic acid C4H6O4 4-5 g / L, sodium acetate CH3COONa 8-9 g / L, KIO3 1-2 mg / L, glycine C2H5NO2 8-10 g / L, and water is used as the solvent; plating is performed at room temperature for 80-90 min.

[0009] Further, in step (3), under the heat preservation and pressure preservation state, the volume ratio of hydrogen to argon in the furnace is hydrogen:argon = 100:4~6; the temperature is 400~450℃, the pressure in the furnace is 400~420Pa, the ignition voltage is 700~750V, and the heat preservation and pressure preservation time is 8~10h.

[0010] Further, in step (4), the heating and melting temperature is 1150-1170°C, and the mass of the additive powder added is 0.03%-0.05% of the mass of the cathode copper block.

[0011] Further, in step (5), the annealing process involves heating to 250±10℃ and holding for 60-70 minutes, then cooling to room temperature in the furnace, and polishing to remove the surface oxide scale to obtain the high-strength oxygen-free copper rod.

[0012] The beneficial effects of this invention are as follows: the oxygen-free copper rod material prepared by the method described in this invention has good strength, exhibiting high tensile strength, and can better meet the requirements of modern industry for the mechanical properties of high-quality copper materials. This invention further improves the strength of cast oxygen-free copper by adding the prepared additive powder. First, this invention introduces chromium and cerium elements into the cathode copper. Chromium and cerium can promote the further precipitation of impurity elements in copper, forming fine metallic compounds distributed in the copper matrix or segregating at the two-phase interface, thus achieving a second-phase strengthening effect. Subsequently, by coating with phosphorus-nickel, the surface of the additive powder can act as non-uniform nucleation sites, promoting the nucleation process and increasing the strength of the material. Since it is difficult to directly coat the surface of copper alloys with nickel, it is first activated with zinc powder in an acidic environment. During the activation process, the copper alloy powder and zinc powder form a galvanic cell structure. Zinc dissolves and releases electrons, which are transferred to the copper alloy powder, depositing an activation layer of nickel on the surface of the copper alloy powder, providing conditions for subsequent phosphorus-nickel coating. Subsequently, in a glow discharge plasma environment, argon bombardment of the titanium mesh causes titanium atoms to be released and diffuse to the surface of the additive powder, forming a titanium-containing layer. This promotes the rapid fusion of the additive powder and the copper melt, reduces the generation of defects, and thus improves the strength of the material. Attached Figure Description

[0013] Figure 1 A comparison graph showing the tensile strength of oxygen-free copper rods prepared by the methods described in the various embodiments and comparative examples. Detailed Implementation

[0014] Example 1

[0015] A method for preparing high-strength oxygen-free copper rods, comprising the following steps: (1) The copper-chromium master alloy powder and the copper-cerium master alloy powder are passed through a 500-mesh sieve, and the sieved powders are collected and mixed evenly to obtain a mixed powder. In the copper-chromium master alloy powder, the mass percentage of chromium is 10% and the balance is copper; in the copper-cerium master alloy powder, the mass percentage of cerium is 20% and the balance is copper. The mass ratio of the mixed powders after sieving is copper-chromium master alloy powder: copper-cerium master alloy powder = 10:2. The mixed powder is added to acetone, cleaned and degreased under ultrasonic conditions, and then subjected to solid-liquid separation. The solid phase is kept at 100℃. The solid phase was dried for 1 hour, and then washed with an alkaline solution of sodium hydroxide, trisodium phosphate, and sodium silicate. The concentration of sodium hydroxide in the alkaline solution was 16 g / L, the concentration of trisodium phosphate was 20 g / L, the concentration of sodium silicate was 5 g / L, and the solvent was water. The alkaline washing temperature was 80°C, the alkaline washing time was 5 min, and reflux was carried out during the alkaline washing process. After the alkaline washing was completed, the solid and liquid were separated. The solid phase was washed with deionized water until the washing liquid was neutral, and then dried at 100°C for 1 hour to obtain the cleaned powder. (2) The cleaned powder is added to an oxalic acid solution for acid washing. The concentration of oxalic acid in the oxalic acid solution is 8 g / L, the solvent is water, and the acid washing time is 120 s. After acid washing, solid and liquid are separated. The solid phase is washed with deionized water until the washing liquid is neutral, and then dried at 100°C for 1 h. The dried solid phase is mixed with zinc powder that has passed through a 500-mesh sieve. Then the mixture is added to an activation solution for activation treatment. The activation treatment process is as follows: First, a mixed aqueous solution of sodium citrate, citric acid, and nickel chloride is prepared as the activation solution. The solution is heated to 70°C in a water bath and kept at that temperature, then refluxed. Then, the mixture is added to the solution. In the mixed aqueous solution of sodium citrate, citric acid, and nickel chloride, the concentration of sodium citrate is 120 g / L, the concentration of citric acid is 80 g / L, and the concentration of nickel chloride is 3 g / L. The ratio of the mixture added to the mixed aqueous solution of sodium citrate, citric acid, and nickel chloride is: mixture: sodium citrate, citric acid, ... The mixed aqueous solution of nickel chloride is 1g:50mL; after the addition is complete, continue to keep it at 70℃ for 90s to complete the activation; the mass ratio of the dried solid phase to the sieved zinc powder is 10:6; after activation, the solid and liquid are separated, the solid phase is washed 3 times with deionized water, dried at 100℃ for 1h, and then subjected to electroless phosphorus-nickel plating. In the electroless phosphorus-nickel plating, the concentrations of each component in the plating solution are: NiSO4·6H2O 20g / L, Na The concentrations of H2PO2·H2O were 25 g / L, sodium citrate hydrate (C6H5Na3O7·2H2O) was 14 g / L, succinic acid (C4H6O4) was 4 g / L, sodium acetate (CH3COONa) was 8 g / L, KIO3 was 1 mg / L, glycine (C2H5NO2) was 8 g / L, and water was used as the solvent. The solid-liquid ratio was 1 g of the dried solid phase to 100 mL of the plating solution. The plating was carried out at room temperature for 80 min to obtain a phosphorus-nickel coated composite powder. (3) The phosphorus-nickel composite powder is laid on the cathode plate of the glow discharge plasma furnace. A titanium mesh is placed on the outside of the phosphorus-nickel composite powder. After the furnace is covered, the air inside the furnace is extracted and a mixture of hydrogen and argon is introduced as a reducing atmosphere. The voltage and duty cycle are set to start the glow discharge. After the temperature rises to a specific value, the furnace is kept warm and pressurized. Under the heat preservation and pressure preservation conditions, the volume ratio of hydrogen to argon in the furnace is hydrogen:argon = 100:4; the temperature is 400℃; the pressure inside the furnace is 400Pa; the glow discharge voltage is 750V; and the heat preservation and pressure preservation time is 8h. After the treatment is completed, the gas supply is turned off and the furnace is cooled to obtain the additive powder. (4) The cathode copper block is heated to 1150°C in a vacuum medium frequency induction furnace and melted. After melting, the additive powder is added. The mass of the additive powder added is 0.03% of the mass of the cathode copper block. After electromagnetic stirring for 3 minutes, it is immediately cast into an ingot. After casting, it is covered with graphite flakes and cooled. (5) The cooled ingot is annealed by heating to 250°C and holding for 60 minutes, then cooling to room temperature in the furnace, and grinding to remove the surface oxide scale to obtain the high-strength oxygen-free copper rod.

[0016] Example 2

[0017] A method for preparing high-strength oxygen-free copper rods, comprising the following steps: (1) The copper-chromium master alloy powder and the copper-cerium master alloy powder are passed through a 500-mesh sieve, and the sieved powders are collected and mixed evenly to obtain a mixed powder. In the copper-chromium master alloy powder, the mass percentage of chromium is 10% and the balance is copper; in the copper-cerium master alloy powder, the mass percentage of cerium is 20% and the balance is copper. The mass ratio of the mixed powders after sieving is copper-chromium master alloy powder: copper-cerium master alloy powder = 10:2. The mixed powder is added to acetone, cleaned and degreased under ultrasonic conditions, and then subjected to solid-liquid separation. The solid phase is kept at 100℃. The solid phase was dried for 1 hour, and then washed with an alkaline solution of sodium hydroxide, trisodium phosphate, and sodium silicate. The concentration of sodium hydroxide in the alkaline solution was 17 g / L, the concentration of trisodium phosphate was 20 g / L, the concentration of sodium silicate was 6 g / L, and the solvent was water. The alkaline washing temperature was 80°C, and the alkaline washing time was 5 minutes. The reflux was used during the alkaline washing process. After the alkaline washing was completed, the solid and liquid were separated. The solid phase was washed with deionized water until the washing liquid was neutral, and then dried at 100°C for 1 hour to obtain the cleaned powder. (2) The cleaned powder is added to an oxalic acid solution for acid washing. The concentration of oxalic acid in the oxalic acid solution is 9 g / L, the solvent is water, and the acid washing time is 120 s. After acid washing, solid and liquid are separated. The solid phase is washed with deionized water until the washing liquid is neutral, and then dried at 100°C for 1 h. The dried solid phase is mixed with zinc powder that has passed through a 500-mesh sieve. The mixture is then added to an activation solution for activation treatment. The activation treatment process is as follows: First, a mixed aqueous solution of sodium citrate, citric acid, and nickel chloride is prepared as the activation solution. The solution is heated to 70°C in a water bath and kept at that temperature, then refluxed. Then, the mixture is added to the solution. In the mixed aqueous solution of sodium citrate, citric acid, and nickel chloride, the concentration of sodium citrate is 120 g / L, the concentration of citric acid is 80 g / L, and the concentration of nickel chloride is 3 g / L. The ratio of the mixture added to the mixed aqueous solution of sodium citrate, citric acid, and nickel chloride is: mixture: sodium citrate, citric acid, ... The mixed aqueous solution of nickel chloride is 1g:50mL; after the addition is complete, continue to keep it at 70℃ for 90s to complete the activation; the mass ratio of the dried solid phase to the sieved zinc powder is 10:7; after activation, the solid and liquid are separated, the solid phase is washed 3 times with deionized water, dried at 100℃ for 1h, and then subjected to electroless phosphorus-nickel plating. In the electroless phosphorus-nickel plating, the concentrations of each component in the plating solution are: NiSO4·6H2O 20g / L, Na The concentrations of H2PO2·H2O were 25 g / L, sodium citrate hydrate (C6H5Na3O7·2H2O) was 14 g / L, succinic acid (C4H6O4) was 4 g / L, sodium acetate (CH3COONa) was 8 g / L, KIO3 was 1 mg / L, and glycine (C2H5NO2) was 9 g / L. The solvent was water. The solid-liquid ratio was 1 g of dried solid phase to 100 mL of plating solution. The plating was carried out at room temperature for 80 min to obtain a phosphorus-nickel coated composite powder. (3) The phosphorus-nickel composite powder is laid on the cathode plate of the glow discharge plasma furnace. A titanium mesh is placed on the outside of the phosphorus-nickel composite powder. After the furnace is covered, the air inside the furnace is extracted and a mixture of hydrogen and argon is introduced as a reducing atmosphere. The voltage and duty cycle are set to start the glow discharge. After the temperature rises to a specific value, the furnace is kept warm and pressurized. Under the heat preservation and pressure preservation conditions, the volume ratio of hydrogen to argon in the furnace is hydrogen:argon = 100:5; the temperature is 400℃; the pressure inside the furnace is 400Pa; the glow discharge voltage is 750V; and the heat preservation and pressure preservation time is 9h. After the treatment is completed, the gas supply is turned off and the furnace is cooled to obtain the additive powder. (4) The cathode copper block is heated to 1160°C in a vacuum medium frequency induction furnace and melted. After melting, the additive powder is added. The mass of the additive powder added is 0.04% of the mass of the cathode copper block. After electromagnetic stirring for 3 minutes, it is immediately cast into an ingot. After casting, it is covered with graphite flakes and cooled. (5) The cooled ingot is annealed by heating to 250°C and holding for 60 minutes, then cooling to room temperature in the furnace, and grinding to remove the surface oxide scale to obtain the high-strength oxygen-free copper rod.

[0018] Example 3

[0019] A method for preparing high-strength oxygen-free copper rods, comprising the following steps: (1) The copper-chromium master alloy powder and the copper-cerium master alloy powder are passed through a 500-mesh sieve, and the sieved powders are collected and mixed evenly to obtain a mixed powder. In the copper-chromium master alloy powder, the mass percentage of chromium is 10% and the balance is copper; in the copper-cerium master alloy powder, the mass percentage of cerium is 20% and the balance is copper. The mass ratio of the mixed powders after sieving is copper-chromium master alloy powder: copper-cerium master alloy powder = 10:3. The mixed powder is added to acetone, cleaned and degreased under ultrasonic conditions, and then subjected to solid-liquid separation. The solid phase is kept at 100℃. The solid phase was dried for 1 hour, and then washed with an alkaline solution of sodium hydroxide, trisodium phosphate, and sodium silicate. The concentration of sodium hydroxide in the alkaline solution was 17 g / L, the concentration of trisodium phosphate was 25 g / L, the concentration of sodium silicate was 7 g / L, and the solvent was water. The alkaline washing temperature was 80°C, the alkaline washing time was 5 min, and reflux was carried out during the alkaline washing process. After the alkaline washing was completed, the solid and liquid were separated. The solid phase was washed with deionized water until the washing liquid was neutral, and then dried at 100°C for 1 hour to obtain the cleaned powder. (2) The cleaned powder is added to an oxalic acid solution for acid washing. The concentration of oxalic acid in the oxalic acid solution is 9 g / L, the solvent is water, and the acid washing time is 100 s. After acid washing, solid and liquid are separated. The solid phase is washed with deionized water until the washing liquid is neutral, and then dried at 100°C for 1 h. The dried solid phase is mixed with zinc powder that has passed through a 500-mesh sieve. Then the mixture is added to an activation solution for activation treatment. The activation treatment process is as follows: First, a mixed aqueous solution of sodium citrate, citric acid, and nickel chloride is prepared as the activation solution. The solution is heated to 70°C in a water bath and kept at that temperature, then refluxed. Then, the mixture is added to the solution. In the mixed aqueous solution of sodium citrate, citric acid, and nickel chloride, the concentration of sodium citrate is 130 g / L, the concentration of citric acid is 85 g / L, and the concentration of nickel chloride is 4 g / L. The ratio of the mixture added to the mixed aqueous solution of sodium citrate, citric acid, and nickel chloride is: mixture: sodium citrate, citric acid, ... The mixed aqueous solution of nickel chloride is 1g:50mL; after the addition is complete, continue to keep it at 70℃ for 90s to complete the activation; the mass ratio of the dried solid phase to the sieved zinc powder is 10:7; after activation, the solid and liquid are separated, the solid phase is washed 3 times with deionized water, dried at 100℃ for 1h, and then subjected to electroless phosphorus-nickel plating. In the electroless phosphorus-nickel plating, the concentrations of each component in the plating solution are: NiSO4·6H2O 25g / L, Na The concentrations of H2PO2·H2O were 28 g / L, sodium citrate hydrate (C6H5Na3O7·2H2O) was 15 g / L, succinic acid (C4H6O4) was 5 g / L, sodium acetate (CH3COONa) was 9 g / L, KIO3 was 2 mg / L, and glycine (C2H5NO2) was 9 g / L. The solvent was water. The solid-liquid ratio was 1 g of dried solid phase to 100 mL of plating solution. The plating was carried out at room temperature for 90 min to obtain a phosphorus-nickel coated composite powder. (3) The phosphorus-nickel composite powder is laid on the cathode plate of the glow discharge plasma furnace. A titanium mesh is placed on the outside of the phosphorus-nickel composite powder. After the furnace is covered, the air inside the furnace is extracted and a mixture of hydrogen and argon is introduced as a reducing atmosphere. The voltage and duty cycle are set to start the glow discharge. After the temperature rises to a specific value, the furnace is kept warm and pressurized. Under the heat preservation and pressure preservation conditions, the volume ratio of hydrogen to argon in the furnace is hydrogen:argon = 100:5; the temperature is 450℃; the pressure inside the furnace is 420Pa; the glow discharge voltage is 750V; and the heat preservation and pressure preservation time is 9h. After the treatment is completed, the gas supply is turned off and the furnace is cooled to obtain the additive powder. (4) The cathode copper block is heated to 1160°C in a vacuum medium frequency induction furnace and melted. After melting, the additive powder is added. The mass of the additive powder added is 0.04% of the mass of the cathode copper block. After electromagnetic stirring for 3 minutes, it is immediately cast into an ingot. After casting, it is covered with graphite flakes and cooled. (5) The cooled ingot is annealed by heating to 250°C and holding for 60 minutes, then cooling to room temperature in the furnace, and grinding to remove the surface oxide scale to obtain the high-strength oxygen-free copper rod.

[0020] Example 4

[0021] A method for preparing high-strength oxygen-free copper rods, comprising the following steps: (1) The copper-chromium master alloy powder and the copper-cerium master alloy powder are passed through a 500-mesh sieve, and the sieved powders are collected and mixed evenly to obtain a mixed powder. In the copper-chromium master alloy powder, the mass percentage of chromium is 10% and the balance is copper; in the copper-cerium master alloy powder, the mass percentage of cerium is 20% and the balance is copper. The mass ratio of the mixed powders after sieving is copper-chromium master alloy powder: copper-cerium master alloy powder = 10:3. The mixed powder is added to acetone, cleaned and degreased under ultrasonic conditions, and then subjected to solid-liquid separation. The solid phase is kept at 100℃. The solid phase was dried for 1 hour, and then washed with an alkaline solution of sodium hydroxide, trisodium phosphate, and sodium silicate. The concentration of sodium hydroxide in the alkaline solution was 18 g / L, the concentration of trisodium phosphate was 25 g / L, the concentration of sodium silicate was 8 g / L, and the solvent was water. The alkaline washing temperature was 80°C, the alkaline washing time was 5 min, and reflux was carried out during the alkaline washing process. After the alkaline washing was completed, the solid and liquid were separated. The solid phase was washed with deionized water until the washing liquid was neutral, and then dried at 100°C for 1 hour to obtain the cleaned powder. (2) The cleaned powder is added to an oxalic acid solution for acid washing. The concentration of oxalic acid in the oxalic acid solution is 10 g / L, the solvent is water, and the acid washing time is 100 s. After acid washing, solid and liquid are separated. The solid phase is washed with deionized water until the washing liquid is neutral, and then dried at 100°C for 1 h. The dried solid phase is mixed with zinc powder that has passed through a 500-mesh sieve. Then the mixture is added to an activation solution for activation treatment. The activation treatment process is as follows: First, a mixed aqueous solution of sodium citrate, citric acid, and nickel chloride is prepared as the activation solution. The solution is heated to 70°C in a water bath and kept at that temperature, then refluxed. Then, the mixture is added to the solution. In the mixed aqueous solution of sodium citrate, citric acid, and nickel chloride, the concentration of sodium citrate is 130 g / L, the concentration of citric acid is 85 g / L, and the concentration of nickel chloride is 4 g / L. The ratio of the mixture added to the mixed aqueous solution of sodium citrate, citric acid, and nickel chloride is: mixture: sodium citrate, citric acid, ... The mixed aqueous solution of nickel chloride is 1g:50mL; after the addition is complete, continue to keep it at 70℃ for 90s to complete the activation; the mass ratio of the dried solid phase to the sieved zinc powder is 10:8; after activation, the solid and liquid are separated, the solid phase is washed 3 times with deionized water, dried at 100℃ for 1h, and then subjected to electroless phosphorus-nickel plating. In the electroless phosphorus-nickel plating, the concentrations of each component in the plating solution are: NiSO4·6H2O 25g / L, NaH The concentrations of sodium citrate (C6H5Na3O7·2H2O) were 28 g / L, sodium citrate hydrate (C4H6O4) was 15 g / L, succinic acid (C4H6O4) was 5 g / L, sodium acetate (CH3COONa) was 9 g / L, KIO3 was 2 mg / L, and glycine (C2H5NO2) was 10 g / L. The solvent was water. The solid-liquid ratio was 1 g of dried solid phase to 100 mL of plating solution. The plating was carried out at room temperature for 90 min to obtain a phosphorus-nickel coated composite powder. (3) The phosphorus-nickel composite powder is laid on the cathode plate of the glow discharge plasma furnace. A titanium mesh is placed on the outside of the phosphorus-nickel composite powder. After the furnace is covered, the air inside the furnace is extracted and a mixture of hydrogen and argon is introduced as a reducing atmosphere. The voltage and duty cycle are set to ignite the glow discharge. After the temperature rises to a specific value, the furnace is kept warm and pressurized. Under the heat preservation and pressure preservation conditions, the volume ratio of hydrogen to argon in the furnace is hydrogen:argon = 100:6; the temperature is 450℃; the pressure inside the furnace is 420Pa; the ignition voltage is 750V; and the heat preservation and pressure preservation time is 10h. After the treatment is completed, the gas supply is turned off and the furnace is cooled to obtain the additive powder. (4) The cathode copper block is heated to 1170°C in a vacuum medium frequency induction furnace and melted. After melting, the additive powder is added. The mass of the additive powder added is 0.05% of the mass of the cathode copper block. After electromagnetic stirring for 3 minutes, it is immediately cast into an ingot. After casting, it is covered with graphite flakes and cooled. (5) The cooled ingot is annealed by heating to 250°C and holding for 60 minutes, then cooling to room temperature in the furnace, and grinding to remove the surface oxide scale to obtain the high-strength oxygen-free copper rod.

[0022] Comparative Example 1 A comparative method for preparing oxygen-free copper rods includes the following steps: (1) Pass the copper-chromium master alloy powder through a 500-mesh sieve and collect the sieved powder; the mass percentage of chromium in the copper-chromium master alloy powder is 10%, and the remainder is copper; the sieved powder is added to acetone, cleaned and degreased under ultrasonic conditions, and then the solid and liquid are separated. The solid phase is dried at 100°C for 1 hour. The dried solid phase is added to a composite solution of sodium hydroxide, trisodium phosphate, and sodium silicate for alkaline washing. The concentration of sodium hydroxide in the composite solution of sodium hydroxide, trisodium phosphate, and sodium silicate is 17 g / L, the concentration of trisodium phosphate is 25 g / L, the concentration of sodium silicate is 7 g / L, and the solvent is water; the alkaline washing temperature is 80°C, the alkaline washing time is 5 min, and reflux is condensed during the alkaline washing process; after the alkaline washing is completed, the solid and liquid are separated, and the solid phase is washed with deionized water until the washing liquid is neutral, and then dried at 100°C for 1 hour to obtain the cleaned powder. (2) The cleaned powder is added to an oxalic acid solution for acid washing. The concentration of oxalic acid in the oxalic acid solution is 9 g / L, the solvent is water, and the acid washing time is 100 s. After acid washing, solid and liquid are separated. The solid phase is washed with deionized water until the washing liquid is neutral, and then dried at 100°C for 1 h. The dried solid phase is mixed with zinc powder that has passed through a 500-mesh sieve. Then the mixture is added to an activation solution for activation treatment. The activation treatment process is as follows: First, a mixed aqueous solution of sodium citrate, citric acid, and nickel chloride is prepared as the activation solution. The solution is heated to 70°C in a water bath and kept at that temperature, then refluxed. Then, the mixture is added to the solution. In the mixed aqueous solution of sodium citrate, citric acid, and nickel chloride, the concentration of sodium citrate is 130 g / L, the concentration of citric acid is 85 g / L, and the concentration of nickel chloride is 4 g / L. The ratio of the mixture added to the mixed aqueous solution of sodium citrate, citric acid, and nickel chloride is: mixture: sodium citrate, citric acid, ... The mixed aqueous solution of nickel chloride is 1g:50mL; after the addition is complete, continue to keep it at 70℃ for 90s to complete the activation; the mass ratio of the dried solid phase to the sieved zinc powder is 10:7; after activation, the solid and liquid are separated, the solid phase is washed 3 times with deionized water, dried at 100℃ for 1h, and then subjected to electroless phosphorus-nickel plating. In the electroless phosphorus-nickel plating, the concentrations of each component in the plating solution are: NiSO4·6H2O 25g / L, Na The concentrations of H2PO2·H2O were 28 g / L, sodium citrate hydrate (C6H5Na3O7·2H2O) was 15 g / L, succinic acid (C4H6O4) was 5 g / L, sodium acetate (CH3COONa) was 9 g / L, KIO3 was 2 mg / L, and glycine (C2H5NO2) was 9 g / L. The solvent was water. The solid-liquid ratio was 1 g of dried solid phase to 100 mL of plating solution. The plating was carried out at room temperature for 90 min to obtain a phosphorus-nickel coated composite powder. (3) The phosphorus-nickel composite powder is laid on the cathode plate of the glow discharge plasma furnace. A titanium mesh is placed on the outside of the phosphorus-nickel composite powder. After the furnace is covered, the air inside the furnace is extracted and a mixture of hydrogen and argon is introduced as a reducing atmosphere. The voltage and duty cycle are set to start the glow discharge. After the temperature rises to a specific value, the furnace is kept warm and pressurized. Under the heat preservation and pressure preservation conditions, the volume ratio of hydrogen to argon in the furnace is hydrogen:argon = 100:5; the temperature is 450℃; the pressure inside the furnace is 420Pa; the glow discharge voltage is 750V; and the heat preservation and pressure preservation time is 9h. After the treatment is completed, the gas supply is turned off and the furnace is cooled to obtain the additive powder. (4) The cathode copper block is heated to 1160°C in a vacuum medium frequency induction furnace and melted. After melting, the additive powder is added. The mass of the additive powder added is 0.04% of the mass of the cathode copper block. After electromagnetic stirring for 3 minutes, it is immediately cast into an ingot. After casting, it is covered with graphite flakes and cooled. (5) The cooled ingot is annealed by heating to 250°C and holding for 60 minutes, then cooling to room temperature in the furnace, and grinding to remove the surface oxide scale to obtain the oxygen-free copper rod described in this comparative example.

[0023] Comparative Example 2 A comparative method for preparing oxygen-free copper rods includes the following steps: (1) The copper-chromium master alloy powder and the copper-cerium master alloy powder are passed through a 500-mesh sieve, and the sieved powders are collected and mixed evenly to obtain a mixed powder. In the copper-chromium master alloy powder, the mass percentage of chromium is 10% and the balance is copper; in the copper-cerium master alloy powder, the mass percentage of cerium is 20% and the balance is copper. The mass ratio of the mixed powders after sieving is copper-chromium master alloy powder: copper-cerium master alloy powder = 10:3. The mixed powder is added to acetone, cleaned and degreased under ultrasonic conditions, and then subjected to solid-liquid separation. The solid phase is kept at 100℃. The solid phase was dried for 1 hour, and then washed with an alkaline solution of sodium hydroxide, trisodium phosphate, and sodium silicate. The concentration of sodium hydroxide in the alkaline solution was 17 g / L, the concentration of trisodium phosphate was 25 g / L, the concentration of sodium silicate was 7 g / L, and the solvent was water. The alkaline washing temperature was 80°C, the alkaline washing time was 5 min, and reflux was carried out during the alkaline washing process. After the alkaline washing was completed, the solid and liquid were separated. The solid phase was washed with deionized water until the washing liquid was neutral, and then dried at 100°C for 1 hour to obtain the cleaned powder. (2) The cleaned powder is added to an oxalic acid solution for acid washing. The concentration of oxalic acid in the oxalic acid solution is 9 g / L, the solvent is water, and the acid washing time is 100 s. After acid washing, solid and liquid are separated. The solid phase is washed with deionized water until the washing liquid is neutral, and then dried at 100°C for 1 h. The dried solid phase is mixed with zinc powder that has passed through a 500-mesh sieve. Then the mixture is added to an activation solution for activation treatment. The activation treatment process is as follows: First, a mixed aqueous solution of sodium citrate, citric acid, and nickel chloride is prepared as the activation solution. The solution is heated to 70°C in a water bath and kept at that temperature, then refluxed. Then, the mixture is added to the solution. In the mixed aqueous solution of nickel chloride, the concentration of sodium citrate is 130 g / L, the concentration of citric acid is 85 g / L, and the concentration of nickel chloride is 4 g / L. The ratio of the mixture added to the mixed aqueous solution of sodium citrate, citric acid, and nickel chloride is 1 g: 50 mL. After the addition is completed, the mixture is kept at 70°C for 90 seconds to complete the activation. The mass ratio of the dried solid phase to the sieved zinc powder is 10:7. After activation, the solid and liquid are separated, the solid phase is washed three times with deionized water, and dried at 100°C for 1 hour to obtain the activated composite powder of this comparative example. (3) The activated composite powder is laid on the cathode plate of the glow plasma furnace. A titanium mesh is placed on the outside of the activated composite powder. After the furnace is covered, the air inside the furnace is extracted and a mixture of hydrogen and argon is introduced as a reducing atmosphere. The voltage and duty cycle are set to ignite the glow plasma. After the temperature rises to a specific value, the furnace is kept warm and pressurized. Under the heat preservation and pressure preservation conditions, the volume ratio of hydrogen to argon in the furnace is hydrogen:argon = 100:5; the temperature is 450℃; the pressure inside the furnace is 420Pa; the ignition voltage is 750V; and the heat preservation and pressure preservation time is 9h. After the treatment is completed, the gas supply is turned off and the furnace is cooled to obtain the additive powder. (4) The cathode copper block is heated to 1160°C in a vacuum medium frequency induction furnace and melted. After melting, the additive powder is added. The mass of the additive powder added is 0.04% of the mass of the cathode copper block. After electromagnetic stirring for 3 minutes, it is immediately cast into an ingot. After casting, it is covered with graphite flakes and cooled. (5) The cooled ingot is annealed by heating to 250°C and holding for 60 minutes, then cooling to room temperature in the furnace, and grinding to remove the surface oxide scale to obtain the oxygen-free copper rod described in this comparative example.

[0024] Comparative Example 3 A comparative method for preparing oxygen-free copper rods includes the following steps: (1) The copper-chromium master alloy powder and the copper-cerium master alloy powder are passed through a 500-mesh sieve, and the sieved powders are collected and mixed evenly to obtain a mixed powder. In the copper-chromium master alloy powder, the mass percentage of chromium is 10% and the balance is copper; in the copper-cerium master alloy powder, the mass percentage of cerium is 20% and the balance is copper. The mass ratio of the mixed powders after sieving is copper-chromium master alloy powder: copper-cerium master alloy powder = 10:3. The mixed powder is added to acetone, cleaned and degreased under ultrasonic conditions, and then subjected to solid-liquid separation. The solid phase is kept at 100℃. The solid phase was dried for 1 hour, and then washed with an alkaline solution of sodium hydroxide, trisodium phosphate, and sodium silicate. The concentration of sodium hydroxide in the alkaline solution was 17 g / L, the concentration of trisodium phosphate was 25 g / L, the concentration of sodium silicate was 7 g / L, and the solvent was water. The alkaline washing temperature was 80°C, the alkaline washing time was 5 min, and reflux was carried out during the alkaline washing process. After the alkaline washing was completed, the solid and liquid were separated. The solid phase was washed with deionized water until the washing liquid was neutral, and then dried at 100°C for 1 hour to obtain the cleaned powder. (2) The cleaned powder is added to an oxalic acid solution for acid washing. The concentration of oxalic acid in the oxalic acid solution is 9 g / L, the solvent is water, and the acid washing time is 100 s. After acid washing, solid and liquid are separated. The solid phase is washed with deionized water until the washing liquid is neutral, and then dried at 100°C for 1 h. The dried solid phase is mixed with zinc powder that has passed through a 500-mesh sieve. Then the mixture is added to an activation solution for activation treatment. The activation treatment process is as follows: First, a mixed aqueous solution of sodium citrate, citric acid, and nickel chloride is prepared as the activation solution. The solution is heated to 70°C in a water bath and kept at that temperature, then refluxed. Then, the mixture is added to the solution. The concentration of sodium citrate in the mixed aqueous solution of sodium citrate, citric acid, and nickel chloride is 130 g / L, the concentration of citric acid is 85 g / L, and the concentration of nickel chloride is 4 g / L. The ratio of the mixture added to the mixed aqueous solution of sodium citrate, citric acid, and nickel chloride is: mixture: mixed aqueous solution of sodium citrate, citric acid, and nickel chloride. Solution ratio: 1g:50mL; after adding the material, continue to maintain the temperature at 70℃ for 90s to complete the activation; the mass ratio of the dried solid phase to the sieved zinc powder is 10:7; after activation, the solid and liquid are separated, the solid phase is washed three times with deionized water, dried at 100℃ for 1h, and then subjected to electroless phosphorus-nickel plating. In the electroless phosphorus-nickel plating, the concentrations of each component in the plating solution are: NiSO4·6H2O 25g / L, NaH2PO2·H2O 25g / L, etc. The concentrations of sodium citrate hydrate (C6H5Na3O7·2H2O) were 28 g / L, sodium citrate hydrate (C6H5Na3O7·2H2O) was 15 g / L, succinic acid (C4H6O4) was 5 g / L, sodium acetate (CH3COONa) was 9 g / L, KIO3 was 2 mg / L, glycine (C2H5NO2) was 9 g / L, and water was used as the solvent. The solid-liquid ratio was 1 g of the dried solid phase to 100 mL of the plating solution. The plating was carried out at room temperature for 90 min to obtain a phosphorus-nickel coated composite powder, which was used as the additive powder in this comparative example. (3) The cathode copper block is heated to 1160°C in a vacuum medium frequency induction furnace and melted. After melting, the additive powder is added. The mass of the additive powder added is 0.04% of the mass of the cathode copper block. After electromagnetic stirring for 3 minutes, it is immediately cast into an ingot. After casting, it is covered with graphite flakes and cooled. (4) The cooled ingot is annealed by heating to 250°C and holding for 60 minutes, then cooling to room temperature in the furnace, and grinding to remove the surface oxide scale to obtain the oxygen-free copper rod described in this comparative example.

[0025] Example 5

[0026] The tensile strength of the oxygen-free copper rods prepared by the methods described in the above embodiments and comparative examples was tested according to the requirements of standard GB / T228.1-2010, with the tensile speed set at 2 mm / min. The structure is as follows... Figure 1 As shown.

[0027] Depend on Figure 1 It is known that the oxygen-free copper rod material prepared by the method described in this invention has good strength, exhibiting high tensile strength, and can better meet the requirements of modern industry for the mechanical properties of high-quality copper materials. This invention further improves the strength of cast oxygen-free copper by adding the prepared additive powder. First, this invention introduces chromium and cerium elements into the cathode copper. Chromium and cerium can promote the further precipitation of impurity elements in copper, forming fine metallic compounds distributed in the copper matrix or segregating at the two-phase interface, thus achieving a second-phase strengthening effect. Subsequently, by coating with phosphorus-nickel, the surface of the additive powder can act as non-uniform nucleation sites, promoting the nucleation process and increasing the strength of the material. Since it is difficult to directly coat nickel onto the surface of copper alloys, it is first activated with zinc powder in an acidic environment. During the activation process, the copper alloy powder and zinc powder form a galvanic cell structure. Zinc dissolves and releases electrons, which are transferred to the copper alloy powder, depositing an activation layer of nickel on the surface of the copper alloy powder, providing conditions for subsequent phosphorus-nickel coating. Subsequently, in a glow discharge plasma environment, argon bombardment of the titanium mesh causes titanium atoms to be released and diffuse to the surface of the additive powder, forming a titanium-containing layer. This promotes the rapid fusion of the additive powder and the copper melt, reduces the generation of defects, and thus improves the strength of the material.

[0028] The technical solutions provided by the present invention have been described in detail above. For those skilled in the art, there will be changes in specific implementation methods and application scope based on the ideas of the embodiments of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.

Claims

1. A method for preparing high-strength oxygen-free copper rods, characterized in that the steps include... include: (1) The copper-chromium master alloy powder and the copper-cerium master alloy powder are sieved separately, and the sieved powders are collected and mixed evenly to obtain a mixed powder. The mixed powder is added to acetone, cleaned and degreased under ultrasonic environment, then the solid and liquid are separated, the solid phase is dried, and the dried solid phase is added to a composite solution of sodium hydroxide, trisodium phosphate and sodium silicate for alkaline washing. After alkaline washing, the solid and liquid are separated, the solid phase is washed with deionized water and dried to obtain the cleaned powder. (2) The cleaned powder is added to oxalic acid solution for pickling treatment. After pickling, solid-liquid separation is performed, solid phase is washed and dried. The dried solid phase is mixed with sieved zinc powder. Then the mixture is added to an activation solution for activation treatment. After activation, solid-liquid separation is performed, solid phase is washed and dried. Then, phosphorus-nickel plating is performed to obtain a phosphorus-nickel coated composite powder. (3) The phosphorus-nickel composite powder is laid on the cathode plate of the glow plasma furnace. The phosphorus-nickel composite powder is covered with a titanium mesh. After the furnace is covered, the air inside the furnace is extracted and a mixture of hydrogen and argon is introduced as a reducing atmosphere. The voltage and duty cycle are set to start glow plasma. After the temperature rises to a specific value, the furnace is kept warm and pressure is maintained. After the process is completed, the gas supply is turned off and the furnace is cooled to obtain the additive powder. (4) The cathode copper block is heated and melted in a vacuum medium frequency induction furnace. After melting, the additive powder is added, and after electromagnetic stirring, it is cast into an ingot. After casting, it is covered with graphite flakes and cooled. (5) The cooled ingot is annealed to obtain the high-strength oxygen-free copper rod.

2. The method for preparing high-strength oxygen-free copper rods according to claim 1, characterized in that, In step (1), the copper-chromium master alloy powder has a chromium mass percentage of 10% and the remainder is copper; the copper-cerium master alloy powder has a cerium mass percentage of 20% and the remainder is copper.

3. The method for preparing high-strength oxygen-free copper rods according to claim 1, characterized in that, In step (1), the mass ratio of the sieved powder mixture is copper-chromium master alloy powder: copper-cerium master alloy powder = 10:2-3; in the composite solution of sodium hydroxide, trisodium phosphate, and sodium silicate, the concentration of sodium hydroxide is 16-18 g / L, the concentration of trisodium phosphate is 20-25 g / L, the concentration of sodium silicate is 5-8 g / L, and the solvent is water; the alkaline washing temperature is 80±5℃, the alkaline washing time is 5-6 min, and condensation and reflux are carried out during the alkaline washing process.

4. The method for preparing high-strength oxygen-free copper rods according to claim 1, characterized in that, In step (2), the concentration of oxalic acid in the oxalic acid solution is 8-10 g / L, the solvent is water, and the pickling time is 100-120 s. The activation process is as follows: first, a mixed aqueous solution of sodium citrate, citric acid, and nickel chloride is prepared as the activation solution, the solution is heated to 70±5℃ in a water bath and kept at that temperature, and then refluxed. Then, the mixture is added to the solution, and after the addition is completed, the temperature is kept at 70±5℃ for 90-120 s to complete the activation. The sieved zinc powder is zinc powder that has passed through a 500-mesh sieve, and the mass ratio of the dried solid phase to the sieved zinc powder is 10:6-8.

5. The method for preparing a high-strength oxygen-free copper rod according to claim 4, characterized in that, In the mixed aqueous solution of sodium citrate, citric acid, and nickel chloride, the concentration of sodium citrate is 120-130 g / L, the concentration of citric acid is 80-85 g / L, and the concentration of nickel chloride is 3-4 g / L; the ratio of the mixture added to the mixed aqueous solution of sodium citrate, citric acid, and nickel chloride is 1 g: 50 mL.

6. The method for preparing high-strength oxygen-free copper rods according to claim 1, characterized in that, In step (2), the concentrations of each component in the electroless phosphorus-nickel plating solution are as follows: NiSO4·6H2O 20-25 g / L, NaH2PO2·H2O 25-28 g / L, sodium citrate hydrate C6H5Na3O7·2H2O 14-15 g / L, succinic acid C4H6O4 4-5 g / L, sodium acetate CH3COONa 8-9 g / L, KIO3 1-2 mg / L, glycine C2H5NO2 8-10 g / L, and water is used as the solvent; plating is performed at room temperature for 80-90 min.

7. The method for preparing high-strength oxygen-free copper rods according to claim 1, characterized in that, In step (3), under the heat preservation and pressure preservation state, the volume ratio of hydrogen to argon in the furnace is hydrogen:argon = 100:4~6; the temperature is 400~450℃, the pressure in the furnace is 400~420Pa, the ignition voltage is 700~750V, and the heat preservation and pressure preservation time is 8~10h.

8. The method for preparing high-strength oxygen-free copper rods according to claim 1, characterized in that, In step (4), the heating and melting temperature is 1150-1170°C, and the mass of the additive powder added is 0.03%-0.05% of the mass of the cathode copper block.

9. The method for preparing high-strength oxygen-free copper rods according to claim 1, characterized in that, In step (5), the annealing process involves heating to 250±10℃ and holding for 60-70 minutes, then cooling to room temperature in the furnace, and polishing to remove the surface oxide scale to obtain the high-strength oxygen-free copper rod.